2013
DOI: 10.3844/ajessp.2013.458.469
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of Agro-Industrials Wastes as Soil Amendments

Abstract: We investigated the fertilizing potential of three agro-industrial wastes (Compost (C), Dehydrated Manures (DM) and Digestate (D)) on soil properties, on seeds germination and the plants growth. Results showed that the addition of wastes modified several soil properties as pH, Electrical Conductivity (EC), Water Retention Capacity (WRC) and Soil Organic Matter (SOM). Hence, SOM increase from 1.5% in unamended soil to 2, 2.3 and to 3.1% in soils amended with (D), with (DM) and with (C) respectively. A fast SOM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…As previously mentioned, no reports on rabbit and sorghum digestate quality have been reported in the open literature constituting this a novel information. Nonetheless, the average values of total solids, K and P for the digestate under study are within the range reported by Vaneeckhaute et al (2013b) and Mekki et al (2013) for digestates of pig manure with energy maize and agriculture wastes, respectively. Table 3 also presents the average value and deviation of all the other analyzed parameters (C, N and H content).…”
Section: Effluents and Biogas Characterization Liquid Digestate Samplsupporting
confidence: 82%
See 2 more Smart Citations
“…As previously mentioned, no reports on rabbit and sorghum digestate quality have been reported in the open literature constituting this a novel information. Nonetheless, the average values of total solids, K and P for the digestate under study are within the range reported by Vaneeckhaute et al (2013b) and Mekki et al (2013) for digestates of pig manure with energy maize and agriculture wastes, respectively. Table 3 also presents the average value and deviation of all the other analyzed parameters (C, N and H content).…”
Section: Effluents and Biogas Characterization Liquid Digestate Samplsupporting
confidence: 82%
“…Table 3 also presents the average value and deviation of all the other analyzed parameters (C, N and H content). Taking into account the value of total C and N determined by elemental analysis, the digestate presents a C/N ratio of 8.1, similar to that reported by Mekki et al (2013), and less than the encountered for the feed stream. Table 3 shows a reduction in the VS content and the carbon content of the digestate with respect to the VS and C in the substrate (see Table 2).…”
Section: Effluents and Biogas Characterization Liquid Digestate Samplsupporting
confidence: 76%
See 1 more Smart Citation